2022
DOI: 10.1111/cns.13946
|View full text |Cite
|
Sign up to set email alerts
|

Specific subsystems of the inferior parietal lobule are associated with hand dysfunction following stroke: A cross‐sectional resting‐state fMRI study

Abstract: Aim The inferior parietal lobule (IPL) plays important roles in reaching and grasping during hand movements, but how reorganizations of IPL subsystems underlie the paretic hand remains unclear. We aimed to explore whether specific IPL subsystems were disrupted and associated with hand performance after chronic stroke. Methods In this cross‐sectional study, we recruited 65 patients who had chronic subcortical strokes and 40 healthy controls from China. Each participant underwent the Fugl‐Meyer Assessment of Han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…In a previous study, application of quadripulse transcranial magnetic stimulation over the SMG was found to decrease excitability of M1, indicating a significant interaction between the two areas 39 . In a recent study, FMA scores showed a positive correlation with the effective connectivity from cSMG to the SMA, and the effective connectivity from cSMG to the ipsilesional superior frontal gyrus was identified as a biomarker for classifying patients with completely paretic hand and those with partially paretic hand 40 . The results of this study in conjunction with those of the present study indicate that the enhanced coupling of cSMG and other functional areas may contribute to motor output of stroke patients, and it may serve as a new target for noninvasive stimulation.…”
Section: Discussionmentioning
confidence: 89%
“…In a previous study, application of quadripulse transcranial magnetic stimulation over the SMG was found to decrease excitability of M1, indicating a significant interaction between the two areas 39 . In a recent study, FMA scores showed a positive correlation with the effective connectivity from cSMG to the SMA, and the effective connectivity from cSMG to the ipsilesional superior frontal gyrus was identified as a biomarker for classifying patients with completely paretic hand and those with partially paretic hand 40 . The results of this study in conjunction with those of the present study indicate that the enhanced coupling of cSMG and other functional areas may contribute to motor output of stroke patients, and it may serve as a new target for noninvasive stimulation.…”
Section: Discussionmentioning
confidence: 89%
“…Differences in the level of impairment, lesion locations, and selection of regions within the complex functional anatomy of the posterior parietal cortex might be influential factors. 38 Also, inter-study variability might lie in the kind of motor tasks used which may drastically differ regarding their recruitment of parietal resources. Hence, this might result in highly variable findings, especially since most studies rely on relatively simple motor tasks rather than complex tasks involving reach and grasp components or fine motor skills of dexterity.…”
Section: Resultsmentioning
confidence: 99%
“…Second, study selection was biased towards the motor domain and, for connectivity studies, towards parieto-frontal connections. Studies with a focus on other domains of deficits, such as aphasia or neglect, and connectivity within posterior parietal brain regions themselves 38 were not in the focus of the present work. For aphasia and neglect, the interested reader is referred to relevant and informative primary research and reviews.…”
Section: Limitationsmentioning
confidence: 99%
“…CON, control group; M-UL, Fugl-Meyer Assessment Upper Limb; MIT, motor imagery training groupEmerging neuroimaging studies have identified neuroimaging biomarkers of functional recovery in stroke patients [39][40][41]. Using multimodal neuroimaging approaches, recent discoveries have revealed brain responses to interventions targeting motor function, including brain atrophy alleviation,42 selective disruption of sensorimotor circuits,43,44 different cortical recruitment patterns,9 and intrinsic brain network reorganization 33. Using task-based fMRI, this longitudinal study explored the unique MIT-related brain reorganization in stroke patients.…”
mentioning
confidence: 99%